Social Integration of Builsa Migrants in Maamobi and Shukura - Agilinko, F. (University of Ghana, 2014)
There has been adequate studies on the social integration of international migrants at their destination but less attention has been dedicated to the area of internal migrants and their social integration in Africa as a whole and Ghana in particular. It was against this background that the present study set out to investigate and examine how migrants are socially integrated in Ghana with the emphasis on Builsa migrants in Accra. The study adopted both quantitative and qualitative approaches with questionnaires and in-depth interviews as the main instruments of the data collection. Only participants who lived in these suburbs for not less than three years and were above 18 years were selected regardless of their social and professional status. The findings of the study showed that, the main motive for migration is employment. On the whole the Builsa migrants are peacefully coexisting with other migrants at the destination and have not encountered serious forms of discrimination from their neighbors most of whom are also migrants. It also emerged that the informal support systems such as the hometown associations helped in the social integration of the respondents amidst the apathy from the educated and the relatively younger respondents. It also came out that those who could speak other languages apart from Buli integrated better than those who could speak only Buli. However, most of the respondents bemoaned the overt manner in which their children are integrating because they have been influenced by the outside trappings of their environment. Another challenge identified was that of lose of identity due to indoctrination. From the emerging findings so far, it can thus be concluded that Ghanaians still have respect for one another since they try to share similar socio-cultural practices and fit into a common environment. It is recommended therefore that, the Ghanaian value system which encourages good neighborliness‘ no matter where one comes from should be upheld and strengthened to ensure a more comprehensive inter-ethnic collaboration for national development while working to identify all internal migrants in the cities in order to provide the needed support for them.
Thesis (MA) - University of Ghana, 2014